The synthesis of 3-methyl-6-R-[1,2,4]triazolo[3,4-b]-[1,3,4]thiadiazole derivatives - Hlazunova, T. V.; Panasenko, O. I.; Knysh, Ye. H.; Глазунова, Тетяна Вікторівна; Панасенко, Олександр Іванович; Книш, Євгеній Григорович (My University, 2020)
derivatives as potential biologically active compounds. Results and discussion. It has been shown that the heterocyclization reaction of 4-amino-5-methyl-4H- 1,2,4-triazole-3-thiol with carboxylic acids in the excess of phosphorus oxychloride yields 3-methyl-6-R-[1,2,4]- triazolo[3,4-b][1,3,4]thiadiazoles. Experimental part. The reaction of 4-amino-5-methyl-4H-1,2,4-triazole-3-thiol with the corresponding carboxylic acids was carried out in the excess of phosphorus oxychloride. The mixture was heated for 5 h with subsequent cooling and neutralization to pH 7 using ammonia solution. 1H NMR spectra of the compounds synthesized were recorded on a Varian Mercury VX-200 spectrometer operating at a frequency of 200 MHz, in DMSO-d6, using tetramethylsilane (TMS) as an internal standard. Melting points were measured using a MPA100 device. The elemental analysis was performed on a Elementar Vario EL Cube elemental analyzer. Agilent 1260 Infinity HPLC System equipped with Agilent 6120 mass spectrometer were used for registering LC-MS data. Conclusions. As a result of this study 10 new compounds of the 3-methyl-6-R-[1,2,4]triazolo[3,4-b][1,3,4]- thiadiazole series have been obtained. The structure and purity of the products have been confirmed using 1Н NMR spectroscopy, LC-MS and elemental analysis. Мета. Синтезувати та підтвердити структуру похідних 3-метил-6-R-[1,2,4]триазоло[3,4-b][1,3,4]тіадіазолу – потенційних біологічно активних сполук. Результати та їх обговорення. Показано, що взаємодія 4-аміно-5-метил-4H-1,2,4-триазол-3-тіолу з карбоновими кислотами у присутності надлишку фосфору оксихлориду перебігає з утворенням 3-метил- 6-R-[1,2,4]триазоло[3,4-b][1,3,4]тіадіазолів. Експериментальна частина. Взаємодію 4-aміно-5-метил-4H-1,2,4-триазол-3-тіолу з карбоновими кислотами проводили у надлишку фосфору оксихлориду при нагріванні впродовж 5 годин з подальшим охолодженням та нейтралізацією до pH 7 розчином амоніаку. 1H ЯМР-спектри синтезованих сполук було записано на спектрометрі Varian Mercury VX-200, робоча частота – 200 MГц, в ДМСО-d6, з використанням тетраметилсилану (TMS) як внутрішнього стандарту. Температури плавлення вимірювали за допомогою пристрою MPA100. Елементний аналіз виконували на елементному аналізаторі Elementar Vario EL Cube. Систему HPLC Agilent 1260 Infinity з мас-спектрометром Agilent 6120 використано для реєстрації LC-MS- даних. Висновки. В результаті дослідження синтезовано 10 нових сполук з ряду похідних 3-метил-6-R-[1,2,4]- триазоло[3,4-b][1,3,4]тіадіазолу. Структуру та чистоту синтезованих сполук підтверджено методами 1Н ЯМР-спектроскопії, LS-MS та елементним аналізом.
Синтез похідних 3-метил-6-R-[1,2,4]триазоло[3,4-b][1,3,4]тіадіазолу
Keywords: synthesis; 1,2,4-triazoles; physicochemical properties; синтез; 1,2,4-триазоли; фізико-хімічні властивості